Lipidomic analysis of non-esterified furan fatty acids and fatty acid compositions in dietary shellfish and salmon by UHPLC/LTQ-Orbitrap-MS. (June 2021) - B. Gowda, Siddabasave Gowda; Minami, Yusuke; Gowda, Divyavani; Furuko, Daisuke; Chiba, Hitoshi; Hui, Shu-Ping
Graphical abstract: Highlights: A UHPLC/LTQ-Orbitrap-MS assisted lipidomic analysis technique was applied. 1st report of identification of non-esterified F-acids in fillets of Japanese dietary shellfish and salmon. Multivariate analysis revealed the species-specific changes in fatty acid compositions. F-acids are found to be abundant in surf clam and salmon trout. A high proportion of PUFAs was detected in fillets of basket clam and salmon trout. Abstract: Lipids such as furan fatty acids (F-acids) are the valuable minor bioactive components of food such as fatty fish and plants. They are reported to have positive health benefits, including antioxidant and anti-inflammatory activities. Despite their importance, limited studies are focusing on F-acid determination in dietary seafood. This study aimed to identify and profile non-esterified F-acids and free fatty acids in total lipid extract of seafood such as shellfish and salmon. The lipidomic analysis using liquid chromatography-linear trap quadrupole-orbitrap mass spectrometry led to identifying seven types of free F-acids in shellfish (n = 5) and salmon (n = 4). The identified F-acids were confirmed by their high-resolution masses and acquired mass spectra. The relative concentrations of F-acids in shellfish range from 0.01 to 10.93 mg/100 g of the fillet, and in salmon, 0.01 to 14.21 mg/100 g of the fillet. The results revealed the highest abundance of F-acids in Sakhalin surf clam, Japanese scallop, and a fatty salmon trout. Besides, relative levels of saturated, monounsaturated, and polyunsaturated fatty acids (PUFAs) in these seafoods were compared with each other, suggesting basket clams and salmon trout to have significantly higher levels of PUFAs. The dietary seafoods enriched with F-acids and PUFAs may have possible health benefits. Hence, the applied technique could be a promising tool for rapid detection and analysis of non-esterified fatty acids in food.